Analysis of Public Health Centre Financing using the District Health Account (DHA) Model in Karangasem District, Bali, Indonesia - Ni Nengah Murniati; Putu Ayu Indrayathi; Pande Putu Januraga (Public Health and Preventive Medicine Archive, 2020)
Background and purpose: Health financing aspects of the public health centres (PHC) may influence the achievement of PHC’s programs and its minimum service standards (SPM). The District Health Account (DHA) is a model used to describe and evaluate health financing at the PHC level. The purpose of this study was to analyze health financing mechanism from both the government and national health insurance in the Karangasem District using the DHA Model. Methods: This study was an evaluation research with a case study approach using the DHA Model. Evaluations were carried out at two PHC, Manggis II PHC and Abang I PHC, between March and April 2018. Data were collected from the Karangasem District Health Office and the PHCs. These include PHC realization data, report on program achievements and SPM. The research instrument used for the data collection and analysis was the DHA extraction form and pivot table which includes information on cost sources, financing managers, service providers, functions, programs, types of activities, budget lines, levels of activities and beneficiaries. Results: We found the source of budget in both PHC was dominated by the district budget (APBD) and the national budget (APBN). The institutions which manage the budget and provide service were predominantly the Health Office and PHC. The most frequent financing functions was for governance and administration, while the largest types of activities covered was the indirect activities. Budget spending for operational costs was higher than for maintenance and investment. Realization of the activity for community program efforts (UKM) and prevention program (UKP) was lower than for the capacity building program. Conclusion: The DHA model was able to identify patterns of health budget allocation by health agencies. The use of the DHA model to analyze health financing should be adopted routinely in order to provide evaluation reports for health agencies at the district level.